Financial scarcity is indirectly related to multiple aspects of executive function through stress and the strength of association depends on childhood poverty. (25th August 2021) - O'Neill, Jessica; Cameron, Claire E.; Leone, Lucia A.; Orom, Heather
Abstract: Financial scarcity, or having insufficient financial resources to meet needs, directly impairs multiple aspects of executive function (EF). Financial scarcity is also stressful and stress impairs EF, however, whether stress mediates the effect of scarcity on EF, and whether these associations vary by either the aspect of EF being measured, or self‐reported developmental history of poverty, is not known. Data were collected from a cross‐sectional sample of 249 female Amazon Mechanical Turk workers who self‐reported their stress using Cohen's perceived stress scale and their EF using the 75‐item Behavior Rating Inventory of Executive Function. They also reported their history of poverty during childhood at ages 0–6, 6–12, and 12–18 years. We measured current financial scarcity using questions that assess five aspects of perceived inability to meet one's basic needs. We used path analysis to test our primary hypothesis that higher financial scarcity is associated with higher stress and more challenges with components of EF overall. Specifically, we tested whether there are indirect effects from scarcity to three specific aspects of EF (behavioral regulation, emotion regulation, and meta‐cognition) through stress. Second, we tested whether the model fit and magnitude of direct effects varied by childhood poverty history. Results supported hypotheses that stress would be negatively associated with multiple EF aspects (behavioral regulation and emotional regulation); and associations were stronger for women reporting early poverty‐related experiences. Interventions designed to alleviate financial scarcity, and address stress management, may be considered as potential ways to support EF for people with scarce financial resources.